Water-foamed polyurethane resin for semi-fireproof building sandwich panels, Semi-fireproof building sandwich panels and Semi-fireproof building sandwich panel boards using the same

KR103035186B1Active Publication Date: 2026-10-21PU SOLUTION CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
KR1020260055249
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2026-03-26
Publication Date
2026-10-21
Estimated Expiration
2046-03-26

Smart Images

  • Figure 112026037311254-PAT00001
    Figure 112026037311254-PAT00001
  • Figure 112026037311254-PAT00002
    Figure 112026037311254-PAT00002
  • Figure 112026037311254-PAT00003
    Figure 112026037311254-PAT00003
Patent Text Reader

Abstract

The present invention relates to a polyurethane resin used in the manufacture of sandwich panels and / or boards, and more specifically, to a polyurethane resin capable of manufacturing architectural sandwich panels and / or boards by water foaming, and to semi-fireproof architectural sandwich panels and / or boards using the same.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to an environmentally friendly and highly flame-retardant water-foamed polyurethane resin and a semi-flame-retardant sandwich panel and / or board for construction using the same. Background Technology

[0003] Generally, architectural panels are used in various buildings, warehouses, and spatial partitions. They must provide a comfortable and hygienic environment, be easy to assemble and disassemble, and possess the characteristics of being lightweight yet strong. Furthermore, they must be made of non-combustible materials to prevent flames from easily spreading to the panels in the event of a fire, and be equipped with functions to block noise.

[0004] Recently, sandwich panels have become widely used as a type of architectural panel. These sandwich panels are laminated panels with a structure in which a filler is inserted between steel plates and fixed with adhesive so that they can be used as interior or exterior building materials. Typically, the surface is mainly made of metal plates such as steel or aluminum plates, and the filler is mainly expanded polystyrene, glass fiber, or urethane, and they are manufactured with consideration for thermal insulation, soundproofing, or thermal insulation.

[0005] However, most conventional building panels, such as sandwich panels and / or boards, are constructed by placing a certain space between two panels or filling the space with insulation or corrugated cardboard, which can block noise to some extent, but there was a problem in that if flames spread to the panel, they could not effectively prevent the fire from spreading, causing the fire to become larger.

[0006] In addition, conventional architectural panels as described above have problems such as being heavy, making transportation and storage difficult, and the assembly and disassembly of the panels are strenuous, resulting in poor workability and long working times.

[0007] In addition, building panels have the problem of being relatively vulnerable to fire compared to cement concrete walls or masonry walls, so a structure to prevent fire spread is required. Prior art literature

[0009] Korean Published Patent Application No. 10-2009-0054021 (May 29, 2009) Korean Registered Patent Application No. 10-2065168 (January 13, 2020) Korean Registered Utility Model No. 20-0380401 (March 22, 2005) The problem to be solved

[0010] The present invention aims to provide a water-foamed polyurethane resin used in the manufacture of semi-fireproof building panels and / or boards, and a semi-fireproof building sandwich panel and / or semi-fireproof building board using the same.

[0011] The technical problems that the present invention aims to solve are not limited to those mentioned above, and other unmentioned problems will be clearly understood by those skilled in the art from the description below. means of solving the problem

[0013] The polyurethane resin of the present invention for solving the above-mentioned problem is a two-component polyurethane resin comprising a resin premix and a curing agent, wherein the resin premix comprises a polyol, a foaming agent, an amine catalyst, a trimerizing catalyst, water, and a flame retardant.

[0014] In addition, the semi-fireproof building sandwich panel and / or board of the present invention comprises a foamed body formed by water-foaming a mixture of the above composition.

[0015] In addition, the present invention relates to a method for manufacturing the above-mentioned semi-fireproof building sandwich panel, comprising: a first step of preparing a resin premix and a curing agent, respectively; a second step of injecting the resin premix and the curing agent into a high-pressure foaming machine, and then foaming and injecting a polyurethane resin mixed with the resin premix and the curing agent into a panel mold inserted into a press using the high-pressure foaming machine; and a third step of demolding the foam from the panel mold after curing. Effects of the invention

[0017] The water-foamed polyurethane resin composition of the present invention utilizes a specific flame retardant, thereby providing a good flame-retardant effect even without the use of a dispersant. Furthermore, as a water-foamed polyurethane resin, it is environmentally friendly and allows for the manufacture of panels using existing production equipment. Additionally, by utilizing this, semi-noncombustible building panels and / or boards with excellent thermal insulation properties can be manufactured in a short period of time. Specific details for implementing the invention

[0019] The present invention will be described in more detail below.

[0020] The semi-noncombustible building sandwich panel or board of the present invention comprises a foamed body formed by water-foaming a water-foamed polyurethane resin, and a method for manufacturing the same comprises: a first step of preparing a resin premix and a curing agent, respectively; a second step of injecting the resin premix and the curing agent into a high-pressure foaming machine, and then foaming and injecting the polyurethane resin mixed with the resin premix and the curing agent into a mold inserted into a press using the high-pressure foaming machine; and a third step of demolding the foamed body from the mold after curing.

[0021] The above mold may be a panel mold or a board mold.

[0023] [Polyurethane Resin]

[0024] This is a step of preparing the resin premix and curing agent, respectively, that constitute the two-component polyurethane resin.

[0025] The above resin premix includes a polyol, a foaming agent, an amine catalyst, a trimerization catalyst, water, and a flame retardant.

[0026] Among the components of the resin premix, the polyol comprises one or more selected from ester polyols, flame-retardant polyols, and PIA (pure isophthalic acid) polyols, preferably two or more, and the combination of polyols is one of the factors affecting cream time and gel time.

[0027] As a preferred embodiment of the polyol combination, the polyol may comprise 4 to 13 weight% of the flame-retardant polyol and the remainder of 100 weight% of the ester polyol, and preferably 4.5 to 11.5 weight% of the flame-retardant polyol and the remainder of 100 weight% of the ester polyol.

[0028] In addition, the polyol may comprise 8 to 15 weight% of the flame-retardant polyol, 40 to 50 weight% of the PIA polyol, and the remainder of 100 weight% of the ester polyol, and preferably, 9.0 to 12.5 weight% of the flame-retardant polyol, 42.0 to 48.0 weight% of the PIA polyol, and the remainder of 100 weight% of the ester polyol.

[0029] In addition, the polyol may comprise 8 to 20 weight% of the flame-retardant polyol and the remainder of 100 weight% of the PIA polyol, and preferably 9.5 to 16.0 weight% of the flame-retardant polyol and the remainder of 100 weight% of the PIA polyol.

[0030] Among the polyol components, the flame-retardant polyol may include a formaldehyde polymer with (chloromethyl)oxirane and 2-methylphenol (Formaldehyde polymer with (chloromethyl)oxirane and 2-methylphenol, Cas No. 1426300-59-5).

[0031] Among the polyol components, the ester polyol may include one or more selected from di(C1-C4 alkylene) glycol-phthalic anhydride and PET-based oligomers, and preferably may include one or more selected from di(C2-C3 alkylene) glycol-phthalic anhydride and PET-based oligomers.

[0032] In addition, the above PET-based oligomer may be a PET-based oligomer with a weight-average molecular weight of 1,200 or less, which is obtained by esterifying an acid component and a diol component in a molar ratio of 1:0.5 to 1.5 and then polymerizing the esterification reaction.

[0033] The above acid component may include one or more selected from terephthalic acid and isophthalic acid, and preferably may include terephthalic acid and isophthalic acid in a weight ratio of 1:0.05 to 0.15.

[0034] In addition, the above diol component may include one or more selected from ethylene glycol, propylene glycol, butylene glycol, and neopentylene glycol, and preferably may include ethylene glycol and neopentylene glycol in a weight ratio of 1:0.1 to 0.2.

[0035] In addition, among the polyol components, the PIA polyol may include a disubstituted carbomonocycle polymer with multialkylene glycol, heteropolycycledione and dialkylene glycol, and preferably may include a disubstituted carbomonocycle polymer with (C1-C7 alkylene) glycol, heteropolycycledione and dialkylene glycol.

[0037] Next, among the resin premix components, the surfactant can be any general surfactant used in the manufacture of urethane resin without limitation, preferably a siloxane poly(C1-C5 alkylene) oxide copolymer can be used, and more preferably a siloxane poly(C3-C5 alkylene) oxide copolymer can be used.

[0038] In addition, the amount used is 1.0 to 5.0 parts by weight, preferably 1.5 to 3.0 parts by weight, per 100 parts by weight of the polyol. At this time, if the amount of foam stabilizer used is less than 1.0 part by weight, there may be a problem of insufficient thermal insulation due to the amount being too small, and if more than 5.0 parts by weight is used, there may be a problem of the physical properties of the product deteriorating due to excessive use.

[0039] Next, the amine catalyst among the resin premix components plays a role in promoting curing and may include one or more selected from dimethyl cyclohexyl amine and 1,4-1,4-diazabicyclo[2.2.2]octane. The amount used is 0.1 to 1.0 parts by weight, preferably 0.2 to 0.8 parts by weight, per 100 parts by weight of polyol. If the amount of amine catalyst used is less than 0.1 parts by weight, the reaction may be very slow and curing may not occur, and there may be a problem with poor moldability. If the amount used exceeds 1.0 parts by weight, the flowability of the urethane resin may be poor due to excessive use, resulting in poor flatness of the manufactured panel or incomplete filling, and the amount of raw material input may increase, which may cause an increase in unit costs; therefore, it is appropriate to use it within the above range.

[0040] Next, the trimerizing catalyst among the resin premix components is used to promote the reaction between the polyol and the curing agent, and may include one or more selected from potassium octoate and 2-hydroxy-propyl-trimethylammonium formate, and may be used in combination. The amount of trimerizing catalyst used is 0.8 to 3.0 parts by weight, preferably 1.0 to 1.8 parts by weight, per 100 parts by weight of polyol. If the amount of trimerizing catalyst used is less than 0.8 parts by weight, there may be a problem where the flame retardancy of the polyurethane resin is reduced or char is not formed due to its use, and if it is used in excess of 23.0 parts by weight, there may be a problem where the flowability of the polyurethane resin is poor due to the reaction being too fast, resulting in incomplete filling and difficulty in producing large panels of 4m or more.

[0041] Next, among the components of the resin premix, the flame retardant plays a role in imparting flame-retardant performance. In the present invention, by using a specific flame retardant, homogeneous flame-retardant performance can be imparted to the entire panel without the use of a dispersant. The flame retardant comprises one or more selected from a phosphorus-based compound represented by the following chemical formula 1, a phosphorus-based compound represented by chemical formula 2, and red phosphorus (cas. 7723-14-0).

[0042] [Chemical Formula 1]

[0043]

[0044] In Formula 1, R is a C2-C5 straight-chain alkylene group, -OCH3CH2-, -OCH(CH3)CH2-, -OCH(CH2CH3)CH2-, or -OCH(CH3)CH2CH2-, preferably a C3-C4 straight-chain alkylene group, -OCH(CH3)CH2- or -OCH(CH2CH3)CH2-, and more preferably -OCH(CH3)CH2-. And, X in Formula 1 is -F, -Cl, or -Br, preferably -Cl.

[0045] [Chemical Formula 2]

[0046]

[0047] In Chemical Formula 2, R 1 is a C1-C3 straight-chain alkyl group, preferably a methyl group. And, R of Chemical Formula 2 2 and R 3 It is a hydrogen atom, a C1-C3 alkyl group, or -CH2CH2C(O)CH3, preferably -CH2CH2C(O)CH3.

[0048] In addition, the amount of flame retardant used is preferably 35 to 70 parts by weight, more preferably 38 to 65 parts by weight, and more preferably 45 to 60 parts by weight, relative to 100 parts by weight of the polyol. At this time, if the amount of flame retardant used is less than 35 parts by weight, it may be difficult to secure sufficient flame retardant performance, and if it exceeds 70 parts by weight, there may be a problem where productivity and workability are reduced due to an increase in defective products caused by a decrease in the flowability of the polyurethane resin due to excessive use. Therefore, it is appropriate to use it within the above range.

[0050] Next, among the components of the resin premix, the water is a component that imparts foaming power to the resin when the resin premix reacts with the curing agent, and it is appropriate to use 2.0 to 8.0 parts by weight, preferably 3.0 to 7.0 parts by weight, and more preferably 3.5 to 6.5 parts by weight per 100 parts by weight of polyol.

[0051] A resin premix can be prepared by adding the previously described polyol, foaming agent, amine catalyst, trimerization catalyst, water, and flame retardant to a mixing tank and mixing for about 30 to 60 minutes using a dissolver or a stirrer.

[0052] In addition, the curing agent in the composition of the two-component polyurethane resin may include one or more selected from MDI (methylene diphenyl diisocyanate), HDI (hexamethylene diisocyanate), and IPDI (isophorone diisocyanate), and preferably may include MDI.

[0054] In the manufacturing method described above, step 2 is a process of introducing the resin premix and hardener prepared in step 1 into a high-pressure foaming machine, and then foaming and injecting the polyurethane resin mixed with the resin premix and hardener into a mold inserted into a press using the high-pressure foaming machine.

[0055] The amount of resin premix and hardener mixed (input amount) fed into the high-pressure foaming machine is 140 to 180 parts by weight of hardener per 100 parts by weight of resin premix, preferably 150 to 175 parts by weight, and more preferably 160 to 175 parts by weight. At this time, if the amount of hardener used is less than 140 parts by weight, char formation is not good and flame retardancy is reduced, which may affect the semi-flammability performance, and if it exceeds 180 parts by weight, there may be a problem where the polyurethane foam becomes too hard and cracks or the panel breaks.

[0056] In addition, the temperatures of the resin premix and the hardener fed into the high-pressure foaming machine are appropriately about 15 to 30°C, preferably 18 to 27°C. Furthermore, the temperature of the press is 45 to 70°C, preferably 45 to 60°C, which is desirable in terms of the smoothness, adhesion, and flowability of the raw resin of the molded panel product.

[0057] Also, when the polyurethane resin is injected into the mold using a high-pressure foaming machine, the foaming pressure is appropriate to be about 100 to 120 bar.

[0058] And, the amount of polyurethane resin injected into the mold by the high-pressure foaming machine is for a mold with a width of 1m 2 Also, when the thickness is 50 mm, it is appropriate to add approximately 2.5 to 2.8 kg of polyurethane resin. In addition, for a width of 1 m 2 And, when the thickness is 75 mm, it is appropriate to input approximately 3.4 to 3.8 kg. Also, a width of 1 m 2 And, when the thickness is 100 mm, it is appropriate to input approximately 4.5 to 5.0 kg. Also, a width of 1 m 2 And when the thickness is 150 mm, it is appropriate to input approximately 6.8 to 7.8 kg. Also, a width of 1 m 2 And when the thickness is 200 mm, it is appropriate to add about 9.0 to 10.0 kg.

[0059] In addition, the above mold may be a mold for panels or a mold for boards, and a mold manufactured by adjusting the thickness of the mold according to whether the product to be manufactured is a sandwich panel or a board is applied.

[0060] Furthermore, the above mold may refer to a mold for a double belt press (or double conveyor belt press). When manufacturing sandwich panels, steel plates are fed into the double belt press for the upper and lower sections, and polyurethane resin is injected and foamed between the upper and lower steel plates. When manufacturing boards, substrates are fed into the double belt press for the upper and lower sections, and polyurethane resin is injected and foamed between the upper and lower substrates. In this case, non-woven fabric, cementitious material, or aluminum foil may be used as the substrate.

[0062] In the manufacturing method described above, step 3 is a process in which the foamed injected polyurethane resin is foamed and cured to form a foamed body, and then demolded from the mold. At this time, the curing time is appropriate as follows: 20 to 25 minutes when the thickness of the panel mold is 50 mm, 25 to 30 minutes when the thickness is 75 mm, 30 to 35 minutes when the thickness is 100 mm, 40 to 45 minutes when the thickness is 125 mm, 50 to 60 minutes when the thickness is 150 mm, and 70 to 80 minutes when the thickness is 200 mm.

[0063] The foam manufactured in this way (semi-noncombustible building sandwich panels and / or boards) has a free-risen density of 50 to 56 kg / m³ 3 , preferably 53.0 ~ 55.0 kg / m² 3 , more preferably 53.5 ~ 54.8 kg / m² 3 It could be.

[0064] The foam manufactured in this way (semi-noncombustible building sandwich panels and / or boards) has a free-risen density of 38.0 to 50.0 kg / m³ 3 , preferably 40.0 ~ 48.0 kg / m² 3, more preferably 40.0 ~ 46.0 kg / m² 3 It could be.

[0065] In addition, the above foam (semi-noncombustible building sandwich panel and / or board) may have a thermal conductivity of 0.025 W / m·k or less when measured according to the KS 4898 method, and preferably a thermal conductivity of 0.015 to 0.024 W / m·k.

[0066] In addition, when the above foam (semi-noncombustible building sandwich panel and / or board) is measured in accordance with the cone calorimeter heat release test and gas toxicity test method of Ministry of Land, Infrastructure and Transport Notification No. 2023-24 (Quality Recognition and Management Standards for Building Materials, etc.), the heat release rate may be 10.0 MJ or less, preferably 4.0 to 9.0 MJ, and the gas toxicity test may be 9 minutes or more, preferably 9 to 14 minutes or more.

[0068] The structure and effects of the present invention will be explained in more detail below through examples. However, the scope of the present invention is not limited to the following examples, and the examples described below are merely illustrative embodiments to enable a specific understanding of the present invention. Parts that are not core components of the present invention can be easily added, omitted, or substituted by a person skilled in the art, and such modified embodiments are also naturally included within the technical concept of the present invention.

[0069] [Example]

[0070] Preparation Example 1: Preparation of Resin Premix

[0071] As a polyol, 95% by weight of ester polyol and 10% by weight of flame-retardant polyol were mixed and prepared.

[0072] As the ester polyol, diethylene glycol-phthalic anhydride (Cas No. 32472-85-8) was used, and as the flame-retardant polyol, a formaldehyde polymer with (chloromethyl)oxirane and 2-methylphenol was used.

[0073] For every 100 parts by weight of the above polyol, 2 parts by weight of a siloxane polyethyleneoxide copolymer as a foaming agent, 0.4 parts by weight of 1,4-diazabicyclo[2.2.2]octane as an amine catalyst, 2.3 parts by weight of potassium octoate as a trimerizing catalyst, and 50 parts by weight of a compound represented by the following chemical formula 1-1 as a flame retardant were used, and 4.0 parts by weight of water was used.

[0074] After adding the above polyol, foaming agent, amine catalyst, trimerization catalyst, water, and flame retardant to a stirring tank, a resin premix was prepared by mixing using a stirrer for about 45 minutes.

[0075] [Chemical Formula 1-1]

[0076]

[0077] In chemical formula 1-1, R is -OCH(CH3)CH2- and X is -Cl.

[0079] Preparation Example 2: Preparation of Resin Premix

[0080] A resin premix was prepared using the same polyol, amine catalyst, foaming agent, water, and flame retardant used in Example 1 above, but with the contents as shown in Table 1 below.

[0081] And, as a PIA polyol, a disubstituted carbon monocycle polymer with multi(C1~C7 alkylene) glycol, heteropolycycledione and dipropylene glycol (Manufacturer: Lotte Chemical) was used.

[0082] The anti-foaming agent used was a siloxane polypropylene oxide copolymer.

[0083] The trimerization catalyst used was 1 part by weight of potassium octoate and 1.2 parts by weight of 2-hydroxy-propyl-trimethyl ammoniumformate.

[0085] Preparation Examples 3–7 and Comparative Preparation Examples 1–3: Preparation of Resin Premixes

[0086] Resin premixes were prepared using the same composition as in Preparation Examples 1 and 2 above, but with the compositions shown in Table 1 below, to carry out Preparation Examples 3 to 7 and Comparative Preparation Examples 1 to 3, respectively. [Chemical Formula 2-1] In Chemical Formula 2-1, R 1 is a methyl group, and R 2 and R 3 It is -CH2CH2C(O)CH3.

[0087] At this time, Comparative Preparation Examples 1 to 4 used a copolymer of siloxane polyethyleneoxide as a foaming agent.

[0088] division Preparation Example 1 Preparation Example 2 Preparation Example 3 Preparation Example 4 Preparation Example 5 Comparison Preparation Example 1 polyol Flame retardant polyol (weight%) 5 10 10 10 10 - Ester polyol (weight%) 95 90 45 - 45 100 PIA Polyol (weight%) - - 45 90 45 - total 100 wt% Polyol (parts by weight) 100 100 100 100 100 100 Jeongpoje Jeongpoje 1 2 - - - - 2 Jeongpoje 2 - 2 2 2 2 - amine catalyst 0.4 0.4 0.4 0.4 0.4 0.4 Trimeric catalyst Trimerization catalyst 1 2.3 1 1 1 1 2.3 Trimeric catalyst 2 - 1.2 1.2 1.5 1.2 - flame retardant Chemical formula 1-1 50 50 50 50 45 50 Chemical formula 2-1 - - - - 10 - 적(cas.7723-14-0) 5 - - water 4.3 4.3 4.4 4.5 4.4 4.0 *Foaming Agent 1: Siloxane polymethylene oxide copolymer *Foaming Agent 2: Siloxane polypropylene oxide copolymer *Trimerization Catalyst 1: Potassium octoate *Trimerization Catalyst 2: 2-hydroxy-propyl-trimethylammonium formate

[0089] division Preparation Example 6 Preparation Example 7 Comparison Preparation Example 2 Comparison Preparation Example 3 polyol flame-retardant polyol 14.5 wt% 8.3 wt% 18.5 wt% 10 wt% ester polyol 37.5 wt% 50.9 wt% 29.0 wt% 45 wt% PIA polyol 48.0 wt% 40.8 wt% 52.5 wt% 45 wt% total 100 wt% Polyol (parts by weight) 100 100 100 100 Jeongpoje Jeongpoje 2 2 2 2 2 amine catalyst 0.4 0.4 0.4 1.5 Trimeric catalyst Trimerization catalyst 1 1 1 1 1 Trimeric catalyst 2 0.4 0.4 0.4 0.4 flame retardant Chemical formula 1-1 45 45 45 50 Chemical formula 2-1 10 10 10 - water 4.4 4.5 4.4 4.5 *Forming Agent 2: Siloxane Polypropylene Oxide Copolymer *Trimeric Catalyst 1: Potassium Octoate *Trimeric Catalyst 2: 2-Hydroxy-propyl-trimethylammonium Formate

[0091] Example 1

[0092] For 100 parts by weight of the 20°C raisin premix of Preparation Example 1 prepared above, 165 parts by weight of 20°C MDI (methylene diphenyl diisocyanate, manufacturer: Kumho, product name: M200) was introduced into a high-pressure foaming machine as a curing agent.

[0093] Then, a polyurethane resin mixed with a resin premix and a curing agent was foam-molded by foaming and injecting it into a panel mold (1 m wide, 4 m long, 125 mm thick) inserted into a 50°C press using the high-pressure foaming machine to form a foamed body.

[0094] Next, after curing for about 60 minutes, the foam was demolded from the panel mold.

[0095] A semi-noncombustible building sandwich panel was manufactured by cleaning the contaminated parts of the demolded foam.

[0097] Examples 2 to 7 and Comparative Examples 1 to 3

[0098] Semi-noncombustible building sandwich panels of the same size and shape were manufactured using the same method as in Example 1 above, and Examples 2 to 3 and Comparative Examples 1 to 2 were carried out respectively as shown in Table 3 below.

[0100] Experimental Example: Measurement of physical properties of a panel (foam)

[0101] The cream time, gel time, free rise density, final density, thermal conductivity, and heat release rate of foamed bodies (panels) made of water-foamed polyurethane resins of Examples 1 to 6 and Comparative Examples 1 to 3 were measured, and the results are shown in Tables 3 and 4 below.

[0102] At this time, the thermal conductivity was measured according to the KS 4898 method.

[0103] In addition, the heat release rate was measured in accordance with the method of Ministry of Land, Infrastructure and Transport Notification No. 2023-24 (Quality Recognition and Management Standards for Building Materials, etc.).

[0104] division Example 1 Example 2 Example 3 Example 4 Example 5 Resin Premix Preparation Example 1 Preparation Example 2 Preparation Example 3 Preparation Example 4 Preparation Example 5 100 parts by weight hardener 165 parts by weight Cream Time 15 seconds 14 seconds 15 seconds 15 seconds 21 seconds Gel time 33 seconds 33 seconds 34 seconds 34 seconds 37 seconds Free rise density (kg / m²) 3 ) 43.1 42.8 45.3 43.0 45.1 Final density (kg / m³) 3 ) 46.0 46.1 48.2 45.7 48.8 Thermal conductivity (W / m·k) 0.023 0.023 0.023 0.022 0.020 Heat release rate (MJ) 8.5 6.8 6.3 8.7 5.2

[0105] division Example 6 Example 7 Comparative Example 1 Comparative Example 2 Comparative Example 3 Resin Premix Preparation Example 6 Preparation Example 7 Comparison Preparation Example 1 Comparison Preparation Example 2 Comparison Preparation Example 3 100 parts by weight hardener 165 parts by weight Cream Time 29 seconds 32 seconds 13 seconds 23 seconds 12 seconds Gel time 180 seconds 180 seconds 32 seconds 38 seconds 30 seconds Free rise density (kg / m²) 3 ) 40.2 45.9 39.5 37.8 45.5 Final density (kg / m³) 3 ) 44.4 50.1 40.4 42.4 48.7 Thermal conductivity (W / m·k) 0.017 0.022 0.045 0.019 0.036 Heat release rate (MJ) 4.8 6.0 14.2 5.7 11.2

[0106] Looking at the experimental results in Tables 3 and 4 above, Examples 1 to 7 have appropriate cream and gel times, with free-rising densities of 38.0 to 50.0 kg / m³. 3 and final density 42.0 kg / m³ 3 It has high mechanical properties and exhibited excellent flame retardancy with a thermal conductivity of 0.025 W / m·k or less and a heat release rate of 10.0 MJ or less.

[0107] In contrast, Comparative Example 1, which used ester polyol alone, had lower cream time and gel time compared to Examples 1 to 7, and also had lower mechanical properties due to its relatively lower density, and showed low flame retardancy with high thermal conductivity and heat release rate.

[0108] A panel (foam) using the resin premix of Comparative Preparation Example 2, which uses three types of polyols, but uses more than 15% by weight of flame-retardant polyol and more than 50% by weight of PIA polyol, showed low thermal conductivity and low heat release rate, indicating excellent flame retardancy, but had a problem in that the free rise density and final density were relatively much lower compared to Example 5.

[0109] In addition, the panel (foam) using the resin premix of Comparative Preparation Example 3, which used three types of polyols, but used less than 8% by weight of flame-retardant polyol and less than 40% by weight of PIA polyol, showed a high thermal conductivity and an excessively high heat release rate, and had a problem of the cream time becoming too short.

Claims

Claim 1 As a two-component polyurethane resin, a resin premix; and a curing agent; wherein the resin premix comprises a polyol, a foaming agent, an amine catalyst, a trimerizing catalyst, water, and a flame retardant, wherein the polyol comprises two or more selected from ester polyols including di(C1-C4 alkylene) glycol-phthalic anhydride, flame retardant polyols, and PIA (pure isophthalic acid) polyols, and the flame retardant polyol comprises a formaldehyde polymer with (chloromethyl)oxirane and 2-methylphenol, and the flame retardant comprises one or more selected from a phosphorus-based compound represented by Chemical Formula 1, a phosphorus-based compound represented by Chemical Formula 2, and red ions; a water-foamed polyurethane resin for semi-noncombustible building sandwich panels [Chemical Formula 1] In Chemical Formula 1, R is -OCH3CH2-, -OCH(CH3)CH2-, -OCH(CH2CH3)CH2- or -OCH(CH3)CH2CH2-, and X is -Cl, [Chemical Formula 2] In Chemical Formula 2, R 1 is a methyl group, and R 2 and R 3 It is a hydrogen atom, a C1-C3 alkyl group, or -CH2CH2C(O)CH3. Claim 2 A water-foamed polyurethane resin for semi-fireproof building sandwich panels according to claim 1, wherein the foaming agent comprises a siloxane polyalkyleneoxide copolymer, the amine catalyst comprises one or more selected from dimethyl cyclohexyl amine and 1,4-diazabicyclo[2.2.2]octane, and the trimerizing catalyst comprises one or more selected from potassium octoate and 2-hydroxy-propyl-trimethyl ammoniumformate. Claim 3 delete Claim 4 delete Claim 5 A water-foamed polyurethane resin for semi-noncombustible building sandwich panels according to claim 1, characterized in that the polyol comprises 4 to 13 weight% of the flame-retardant polyol and the remainder of 100 weight% is the ester polyol, or the polyol comprises 8 to 15 weight% of the flame-retardant polyol, 40 to 50 weight% of the PIA polyol and the remainder of 100 weight% is the ester polyol, or the polyol comprises 8 to 20 weight% of the flame-retardant polyol and the remainder of 100 weight% is the PIA polyol. Claim 6 A water-foamed polyurethane resin for semi-noncombustible building sandwich panels according to claim 1, characterized in that the resin premix comprises, with respect to 100 parts by weight of the polyol, 1.0 to 5.0 parts by weight of a foam stabilizer, 0.1 to 1.0 parts by weight of an amine catalyst, 0.8 to 3.0 parts by weight of a trimer catalyst, 35 to 70 parts by weight of a flame retardant, and 2.0 to 8.0 parts by weight of water. Claim 7 A water-foamed polyurethane resin for semi-fireproof building sandwich panels according to claim 1, characterized in that the curing agent comprises one or more selected from MDI (methylene diphenyl diisocyanate), HDI (hexamethylene diisocyanate), and IPDI (isophorone diisocyanate), and the curing agent is mixed and used in an amount of 140 to 180 parts by weight per 100 parts by weight of the resin premix. Claim 8 A semi-fireproof building sandwich panel characterized by comprising a foamed body formed by water-foaming a polyurethane resin selected from any one of claims 1, 2, and 5 to 7. Claim 9 delete Claim 10 Step 1: preparing a resin premix and a hardener, respectively; Step 2: after introducing the resin premix and hardener into a high-pressure foaming machine, foaming and injecting the polyurethane resin mixed with the resin premix and hardener into a panel mold inserted into a press using the high-pressure foaming machine; A method for manufacturing a semi-noncombustible building sandwich panel comprising a process including the third step of demolding the foam from the panel mold after curing, wherein the resin premix comprises a polyol, a foam stabilizer, an amine catalyst, a trimerizing catalyst, water, and a flame retardant, wherein the polyol comprises two or more selected from ester polyols including di(C1-C4 alkylene) glycol-phthalic anhydride, flame retardant polyols, and PIA (pure isophthalic acid) polyols, and the flame retardant comprises one or more selected from phosphorus-based compounds represented by the following chemical formula 1, phosphorus-based compounds represented by chemical formula 2, and red ions; [Chemical Formula 1] In Chemical Formula 1, R is -OCH3CH2-, -OCH(CH3)CH2-, -OCH(CH2CH3)CH2- or -OCH(CH3)CH2CH2-, and X is -Cl, [Chemical Formula 2] In Chemical Formula 2, R 1 is a methyl group, and R 2 and R 3 It is a hydrogen atom, a C1-C3 alkyl group, or -CH2CH2C(O)CH3.

Citation Information

Patent Citations

  • Preparation method of expansible graphite modified high-flame-retardant rigid polyurethane foam

    CN105218782A

  • Foamer, and method for producing foamed plastic using the same, polyurethane foam, article, system liquid and kit for polyurethane foam

    JP2022039579A

  • Water based polyisocyanurate polyurethane foam composition

    KR1020120074560A